2019
DOI: 10.1016/j.humov.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Is imagery better than reality? Performance in imagined dart throwing

Abstract: We investigated whether deviations from optimal performance are predicted in motor imagery. In Experiment 1, novices and experts imagined and executed dart throws. In imagination, they reported the final position of the dart. Experts performed better than novices in execution and imagination. Distance to the target and bias were smaller in imagination than in execution. In Experiment 2, we dissociated the roles of feedback from proximal and distal action elements for predictions. Three groups of novices estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 49 publications
2
53
0
Order By: Relevance
“…Interestingly, a system comparing visual feedback to simulated visual consequences is critical to planning motor actions (during physical practice) prior to effector selection (i.e., mapping motor representations to an effector), separate from that which generates the efference copy and intended consequences of the movement 66 . In showing that activation in regions previously thought to reflect the reliance on a visual image during motor imagery of a task 67 negatively correlated with improvements in performance (i.e., bilateral parietal cortices and lingual gyri at the mid-training scan; and occipital regions as well as left superior and bilateral middle frontal gyri at the post-training) 40 , our findings may suggest that previously theorized error detection/correction mechanisms active during motor imagery 18 , 68 only supports refinement of effector independent representations, relying on these visual comparisons. This argument is further substantiated by our finding of increased activation localized to occipital–temporal areas observed following training regardless of the order that motor imagery was applied, in line with work examining activation during (imagery-based) pre-shot routines in expert versus novice archers 69 and golfers 70 .…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, a system comparing visual feedback to simulated visual consequences is critical to planning motor actions (during physical practice) prior to effector selection (i.e., mapping motor representations to an effector), separate from that which generates the efference copy and intended consequences of the movement 66 . In showing that activation in regions previously thought to reflect the reliance on a visual image during motor imagery of a task 67 negatively correlated with improvements in performance (i.e., bilateral parietal cortices and lingual gyri at the mid-training scan; and occipital regions as well as left superior and bilateral middle frontal gyri at the post-training) 40 , our findings may suggest that previously theorized error detection/correction mechanisms active during motor imagery 18 , 68 only supports refinement of effector independent representations, relying on these visual comparisons. This argument is further substantiated by our finding of increased activation localized to occipital–temporal areas observed following training regardless of the order that motor imagery was applied, in line with work examining activation during (imagery-based) pre-shot routines in expert versus novice archers 69 and golfers 70 .…”
Section: Discussionmentioning
confidence: 52%
“…These internal predictions, which are the inputs of the forward model to the controller, could improve the output of the controller in the absence of movement-related sensory feedback, and therefore enhance motor performance in a subsequent motor task. However, although forward internal models are engaged during motor imagery, sensorimotor prediction is more variable, since it is not updated by sensory feedbacks, which may explain the difference between PT and MIT groups 59 . Recent findings have demonstrated that motor imagery-based practice drives motor learning of a kinematically complex multi-articular motor skill in the absence of sensory feedback 60 .…”
Section: Discussionmentioning
confidence: 99%
“…From a methodological viewpoint for imagery research, this study contributes to emerging evidence that indicates when MI and ME are compared, it is important to have a condition in which ME is conducted without distal action effects [12,32,40]. An ME condition without distal action effects enables one to distinguish which differences between MI and ME are due to the lack of distal action effects and which differences are due to other mechanisms.…”
Section: Limitations and Perspectivesmentioning
confidence: 94%
“…In many respects, MI seems to rely on similar mechanisms as motor execution (ME) [1,[5][6][7][8][9][10][11][12]. However, there are also differences between MI and ME [11][12][13][14][15][16]. One such difference is that MI requires not only the imagination of the action, but also the imagination of the action effects on the body and the environment.…”
Section: Introductionmentioning
confidence: 99%